PERAN PUSAT LAYANAN USAHA TERPADU KOPERASI USAHA MIKRO KECIL MENENGAH (PLUT KUMKM) KABUPATEN TULUNGAGUNG DALAM MENINGKATKAN PENDAPATAN MASYARAKAT - Muhtar Rifai; Kasih Prihantoro; Panji Suwarno (JURNAL CAFETARIA, 2022)
This study focuses on discussing the role of the integrated business service center for micro, small and medium enterprises (PLUT KUMKM) as a facilitator provided by the government to boost Micro, Small, and Medium Enterprises (MSMEs) in various aspects through the concept of community economic empowerment which is realized in the form of coaching. Guidance consisting of training and product marketing is a step to transform into leading Micro, Small, and Medium Enterprises (MSMEs) according to the progress of the times. The writing of this article uses a descriptive qualitative method which aims to provide an overview of the object under study. Meanwhile, data collection techniques to collect data and information are carried out through observations, interviews, and sources of documents or literature in the form of (books, magazines, journals, etc.) and conclude them objectively. The results of the study explain that to reduce unemployment, the government implements a strategy of empowering the community's potential businesses. The empowerment is not only in terms of funding assistance but also in facilitating the business sector to develop. PLUT KUMKM Tulungagung is a government facilitator in providing integrated sustainable insights, entrepreneurship training, and broader product marketing. The final goal to be achieved in addition to reducing unemployment is to create new small businesses, increase income and per capita equity, and realize regional economic resilience.